Core-shell poly(dopamine) magnetic nanoparticles for the extraction of estrogenic mycotoxins from milk and yogurt prior to LC–MS analysis. (15th January 2017) - González-Sálamo, Javier; Socas-Rodríguez, Bárbara; Hernández-Borges, Javier; Rodríguez-Delgado, Miguel Ángel
Highlights: Core-shell Fe3 O4 @poly(dopamine) m-NPs were used as m-μSPE sorbents. Estrogenic mycotoxins were extracted from dairy products and analyzed by LC–MS. A deproteinization step was developed prior to the m-μSPE extraction procedure. Recoveries were in the range 70–120%, RSD < 16% and LODs in the range 0.2–4.8 μg/L. Abstract: In this work, core-shell poly(dopamine) magnetic nanoparticles synthesized in our laboratory have been applied as dispersive solid-phase extraction (dSPE) sorbent for the extraction of a group of six mycotoxins of interest including zearalenone, α-zearalanol, β-zearalanol, α-zearalenol, β-zearalenol and zearalanone, from complex matrices such as milk (whole and skimmed cow milk and semi-skimmed goat milk) and yogurt (an unsweetened natural yogurt) prior to their LC–MS analysis. 17β-estradiol-D5 was used as internal standard. The procedure includes a deproteinization step prior to the extraction procedure. Matrix-matched calibration and a recovery study were carried out in the selected matrices, providing good linearity, relative recovery values in the range 70–120% with RSDs lower than 16% and LODs between 0.21 and 4.77 μg/L for milk samples and between 0.29 and 4.54 μg/kg for yogurt samples.